Exploring Central and Eastern Europe’s Biotechnology Landscape
XII, 228 p.
Keywords: At a time when the human genome has been sequenced advances in the life sciences seem to have great potential for human health, industry and the environment throughout Central and Eastern Europe (CEE). Still, for some, potential risks and ethical dilemmas remain, surrounding issues such as the appropriate use of GM crops, stem cells, genetic information, the nature of intellectual property and other challenges that come with EU accession. This book is the first of its kind to bring together experts from across Europe to explore the landscape of current life science policy and industrial development in CEE, including implications for economies, regulatory and legal frameworks, health care, ethics and human rights. It will be essential reading for researchers and students in science and technology studies, development, sociology, politics and law, and those interested in life science development in transition economies.